OPTIMAL ROTATION OF TEAK PLANTATION : A CASE STUDY AT THONG PHA PHUM PLANTATION - Sangprapy, Anchalee; Hoamuangkaew, Wuthipol (วารสารวนศาสตร์ไทย, 2022)
The study on optimal rotation of teak plantation with spacing of 4x4 m was carried out at Thong Pha Phum plantation, Kanchanaburi province. The 33 sampled plots were randomly laid out in 11 age classes of teak plantation with ranging from 10 to 26 years, and each age class including 3 sampled plots for good, medium and poor site quality. All trees in each sampled plot were measured their diameter at breast height, diameter at stump, diameter at merchantable height, total height and merchantable height. Results of the study indicated that the optimal rotations of teak in the good site quality and at 5 given discount rates of 4, 6, 8, 10 and 12% were at 44, 44, 36, 10 and 10 years from growing and provided maximized NPV in values of 76,106.60, 28, 359.44, 9,066.79, 4,117.59 and 2,723.77 baht per rai respectively. While the medium site quality, at 4 given discount rates of 4, 6, 8 and 10%, their optimal rotation were at 48, 40, 13 and 13 years from planting, and provide NPV in value of 31, 264.98, 8,717.10, 1,393.48 and 0.40 baht per rai respectively. In addition, the poor site quality, at 3 given discount rates of 4, 6, and 8%, their optimal rotation were the same at 15 years from growing and provided maximized NPV in values of 5,425.95, 2,623.91 and 612.90 baht per rai respectively. The teak plantation which their optimal rotations were at 36, 40, 44 and 48 years provided timber with the large size which suitable for using in many different forms and having high selling price while the teak plantations which their optimal rotations were shorter to be 10, 13 and 15 years, provided rather small timber, so this will face the limitation of utilization and low selling price.